Continuity of the video games’ worlds - Sikora, Wojciech (Hybris, 2019)
The aim of this article is to answer the questions about the essence and continuity of the video games’ worlds. In order to achieve that Roman Ingarden’s formal ontological tools are used. The article consists of four main parts. First two clarify the basic concepts used in the article such as a world and an essence. Next, the conditions of world continuity de- duced from three aspects of identity, namely ‘selfness’, ‘wholeness’ and ‘identity’, are discussed. The last part applies these conditions to chosen instances of video game types.